(untitled) (Indian Journal of Public Health Research & Development, 2021)
Suicide by pesticide poisoning consumption among young and old is preventable. More so in India, since larger population are involved in agriculture and its rampant usage for their cultivation. Also, due to weaker India’s public health infrastructure and prevailing folk medicine practices, makes all the more difficult to save victims and it seems add in to huge burden. Objectives: To estimate pattern of self-poisoning, first AID usage and folk medicine practices influenced by their standard of living. Method: Four primary health centre (PHCs) villages of Hassan taluk were selected by simple random sampling and every fifth houses were considered as study subjects (159). To assess their socio-economic situation, standard of living index (SLI) comprising of their basic amenities was adopted to understand its influence on self-poisoning practices. Results: The mean age of males were 44.23 (95 % CI 39.53 to 48.94) with SD (17.57) and females were 37.40 (95% CI 34.78 to 40.02) with SD (13.41). Traditional medicine (folk medicine) (125/78.6%) was practicing for their immediate self-harm (poison) relief. More than 98% respondents told that they do not have any idea or training towards first AID. 23% in higher living index said victim must be put on their back (p<0.05) for recovery. In logit model, predictors showed odds ratio that favoured an increase of risk for poison consumption for every one unit of increase of their education status and family members respectively- (OR 1.182, 95% CI 0.795-1.956; OR 1.081, 95% CI 0.438-2.666). Conclusion: Neither first AID techniques were taught or put into practice which is imperative for life saving. Middle level study subjects were willing to involve themselves in first AID compared to higher class. Many people do not recognize colour marked symbols on pesticide bottle labels as an indicator of poison.